On the Technological Innovation Chain’s Structure, Formation and Operation - Tu, Chun Yan; Wu, Shao Bo; Peng, Shuang (Applied Mechanics and Materials, 2012)
The technological innovation chain is the innovation system that encircles the core technology and is based on supporting technology. The supporting technology not only includes vertical (the upstream and downstream) complementary supporting technology, but also includes the horizontal supporting technology based on the same technical link. The formation of the technology innovation chain is resulted from the limitedness of the technological knowledge, the complementarity of the products, and the pursuit for economy of velocity of innovation. The operation mechanism of the technological innovation chain includes three ways: which are the operating mechanisms relatively based on innovation platform, patent pool, and the R&D contract.